Analyzing the dialogical leadership style and organizational brilliance through organizational commitment in an academic context - Mohsen Nazarzadeh Zare; Mahdi Namdari Pejman; Davood Ghorooneh (مطالعات مدیریت راهبردی, 2023)
IntroductionDialogical leadership and organizational brilliance are emerging concepts in management and leadership, particularly in the field of human resources management, which holds special significance in today's competitive organizational environment. The open and two-way communication approach of dialogical leadership fosters collaboration among organization members, which can enhance the organization's competitiveness, employee satisfaction, productivity, and cost reduction, and ultimately lead to organizational brilliance. In recent years, Iranian higher education managers have noticed the need for an internationalization approach and competition with foreign universities, as well as domestic competition to attract more resources and achieve better performance. In this context, adopting new leadership styles such as dialogical leadership and focusing on organizational commitment can be effective in achieving excellence and subsequent organizational brilliance. By promoting open communication and collaboration with faculty members, staff, and students, dialogical leadership can increase organizational commitment in the university context, which in turn can enhance the brilliance of the university organization. Despite considerable research on the relationship between dialogical leadership style and organizational brilliance in various organizational contexts, there is still a gap in research regarding the investigation of this leadership style's impact on organizational brilliance in the academic context. Additionally, the mediating role of organizational commitment in the relationship between dialogical leadership style and organizational brilliance requires further investigation, especially the exact role of this factor in this relationship in the academic context. Therefore, this study aims to analyze the impact of the dialogical leadership style on organizational brilliance through organizational commitment in the context of Iran's Farhangian University, which plays a significant role in training expert human capital for Iran's education system.MethodologyTo achieve the study's main objective, a descriptive-correlational approach using structural equation modeling was employed. The study population comprised all faculty and non-faculty employees of Farhangian University of Iran, totaling 980 individuals. Using Cochran's formula and stratified sampling method, 276 participants were selected for the study. Three questionnaires were used to collect data on dialogical leadership, organizational brilliance, and organizational commitment, with reported reliabilities of 0.97, 0.95, and 0.81, respectively, based on Cronbach's alpha coefficient. Descriptive and inferential statistical methods were used for data analysis, using SPSS and Lisrel software.Results and DiscussionThe study's first hypothesis revealed that the dialogical leadership style has a positive impact on organizational brilliance at Iran's Farhangian University. This means that the university's leaders and administrators can achieve human resource excellence by engaging in open communication, exchanging ideas and information, and actively listening to key stakeholders. The second hypothesis of the study demonstrated that the dialogical leadership style has a positive and significant effect on the organizational commitment of Farhangian University employees in Iran.  Dialogical leadership can predict a significant percentage of employees' organizational commitment, and aligning individual employee goals with the university's goals can increase employee autonomy, accountability, and loyalty through effective communication processes. The third hypothesis of the study indicated that organizational commitment has a positive and significant impact on organizational brilliance at Farhangian University in Iran. Organizational commitment can significantly predict excellence in organizational resources, capabilities, and knowledge management, as organizational brilliance focuses on the university's resources and competencies. The fourth hypothesis of the study showed that the dialogical leadership style has a positive and significant impact on the organizational brilliance of Farhangian University in Iran through the organizational commitment of employees. This impact is strong enough to predict organizational brilliance through the two constructs of dialogical leadership and organizational commitment. A leadership style based on interaction, negotiation, and collaborative decision-making can improve employee organizational commitment, leading to improved organizational brilliance.ConclusionIn conclusion, the study's findings highlight the significant impact of dialogical leadership on both organizational commitment and organizational brilliance at Iran's Farhangian University. The study suggests that university managers can enhance organizational commitment and brilliance by encouraging faculty and staff participation in decision-making and planning processes. This approach not only increases organizational commitment among the university's main stakeholders but also leads to an overall improvement in organizational brilliance. The study concludes that dialogical leadership can be an effective leadership style for universities to adapt to changes and achieve excellence in the highly interconnected world.